Está en la página 1de 2

# LT1.

1: LAPLACE TRANSFORMS
BASIC DEFINITION
In your study of Differential Equations so far you have probably solved first and second order
equations using methods such as separation of variables, substitutions, homogeneous equations,
and integrating factor technique.

Transforms are another means of solving some differential equations that may prove too difficult
to solve using the above mentioned methods.

Assumed knowledge for studying Laplace transforms: Differentiation
Integration
Partial fractions
Algebra & Transposition
Exponentials & Logarithm’s

The fundamental rule for Laplace Transforms is:

L[ y (t )] = Y (s ) = ∫e
− st
y (t )dt
0

e.g. 1
Determine the Laplace Transform of y (t ) = constant C using the basic definition.

Soln:

∴ L[ y (t )] = ∫e
− st
.C dt
0

= C ∫ e − st dt
0

 1 
= C − . e − st 
 s 0
 C   C 
=  − .e −∞  −  − .e 0 
 s   s 
e −∞ = 0 & e 0 = 1
 C 
= (0 ) −  − × 1
 s 
C
=
s

LT1.1 – Laplace Transforms: Basic Definition Page 1 of 2 June 2012

e − st   s 4  K   K  =  − .e − 4 s   s  L[ f (t )] K ∴ = . Soln: From the graph we define f (t ) as: 0 0≤t<4 f (t ) =  K t>4 Therefore the transform can be separated into 2 parts.e − 4 s s LT1. 2 A signal that is graphed is given below: f(t) K t 4 Determine the Laplace transform of the above signal. ∞ 4 ∞ ∫e − st f (t )dt = ∫ e − st f (t )dt + ∫ e − st f (t )dt 0 0 4 4 ∞ = ∫ e − st (0 )dt + ∫ e − st (K )dt 0 4 ∞ = 0 + K ∫ e − st dt 4 ∞  1  = K − .g.e.e −∞  −  − .e − 4 s   s   s   K  = (0 ) −  − .1 – Laplace Transforms: Basic Definition Page 2 of 2 June 2012 .